Oral bisphosphonates are associated with reduced mortality in frail older people: a prospective five-year study - Sambrook, P. N.; Cameron, I. D.; Chen, J. S.; March, L. M.; Simpson, J. M.; Cumming, R. G.; Seibel, M. J. (Osteoporosis international, 2011)
Summary In a study of 2005 institutionalized older people, use of oral bisphosphonates was associated with a 27% reduction in risk of death compared to non-users after adjusting for potential confounders. Introduction This study investigated whether reductions in mortality reported in a trial of intravenous zoledronate after hip fracture could be seen in older people taking oral bisphosphonates. Methods Two thousand and five institutionalized older people (mean age 85.7 years) were assessed at baseline and followed up for hip fracture and death for at least 5 years. Cox proportional hazards regression was used to estimate effects of bisphosphonates on risk of death. Results At baseline, 78 subjects were taking oral bisphosphonates. Over 5 years of follow-up, 1,596 participants (80%) died. Use of bisphosphonates was associated with a 27% reduction in risk of death compared to non-users after adjusting for age, gender, type of institution, immobility, number of medications, weight, cognitive function, co-morbidities, and hip fracture incidence during the follow-up period (hazard ratio 0.73; 95% CI, 0.56 to 0.94; P = 0.02). Conclusion Oral bisphosphonates are associated with a reduction in the risk of death in the elderly. The mechanism of effect requires further investigation.